DEVELOPMENT OF DIGITAL COMIC BASED LEARNING MEDIA (CHEMTOON) WITH MARVEL APP ON CORROSION MATERIALS - Alfu, siti Hana Irawarni; Irhamni; Wijayanti, Imas Eva (UIN Mataram, 2024)
This research project aims to design, develop and assess the feasibility of using chemical digital comic learning media (chemtoon) with the Marvel App on corrosion materials. Apart from that, to find out students' responses to digital comic learning media (chemtoon) with the Marvel App on corrosion material. Research uses methods research and development (R&D), with the ADDIE development model. The population of this research is all students in class XII Science. The sampling technique was purposive random sampling, obtained class XII-F Science, totaling 32 students as an experimental class. The results of media validation in developing digital comic-based media in the Marvel App show a Vcount value from media expert validators is greater than Vtable with a value of 0.85 – 0.95 > 0.80 , while the material expert assessment of all aspects shows a value of Vcount greater than Vtable with a value of 0.85 – 1 > 0.80. The results of student responses to digital comics obtained an average percentage of all aspects, namely 91.71%. This shows that the digital comic learning media (Chemtoon) with the Marvel App on corrosion material is valid, suitable for use and helps students' understanding of chemistry in corrosion material.